Dynamics of Policy Networks. The Case of Organic Farming Policy in the Czech Republic. Issue 4 (7th August 2016) - Moschitz, Heidrun; Hrabalova, Andrea; Stolze, Matthias
Abstract: To better understand the potential for successful and long-term establishment of environmental policy, the aim of this paper is to explore the network dynamics of a policy field that has become well established in the EU: organic farming. We look at the dynamics of the organic farming policy network in the Czech Republic over a period of 10 years by applying a comparative formal network analysis. We focused in particular on the distribution of power between actors and how capacities of policy actors have evolved between 2004 (its year of accession to the EU) and 2014. We conclude that the organic farming policy network in the Czech Republic has been highly dynamic and has changed from one that was decidedly influenced by organic sector organizations to a network centralized around the Ministry of Agriculture. However, the organic farming organization managed to maintain its good reputation for competence in organic farming policy, which creates opportunities for the organization to remain active in the policy debate.